Early Onset of Wilson Disease: Diagnostic Challenges. Issue 5 (November 2017) - Wiernicka, Anna; Dądalski, Maciej; Jańczyk, Wojciech; Kamińska, Diana; Naorniakowska, Magdalena; Hüsing-Kabar, Anna; Schmidt, Hartmut; Socha, Piotr
ABSTRACT: Objectives: The aim of the study was to analyze the clinical presentations, diagnosis, and treatment of patients ages ⩽5 years with early onset Wilson disease (WD). Methods: Data from 143 pediatric patients with WD treated at our center between January 1996 and November 2015 were retrospectively analyzed. Results: A review of the 143 pediatric patients with WD identified 21 (10 girls, 11 boys) with first symptoms or abnormal liver function test results at age ⩽5 years. The diagnosis of WD was confirmed in 8 patients younger than 5 years. At baseline the mean serum alanine aminotransferase level was 222 U/L and the mean serum aspartate aminotransferase level was 130 U/L. The mean serum ceruloplasmin concentration in 16 tested patients was <20 mg/dL. Of the 15 patients who underwent urinary copper excretion testing, 8 had levels between 40 and 100 μg/day, with only 4 having levels >100 μg/day. Liver copper quantification was >250 μg/g dry weight in 16 patients. The most common mutation was p.H1069Q, with compound heterozygosity in 5 patients and homozygosity in 9. Sixteen patients were treated with zinc salts and 5 with D-penicillamine. Both treatments were effective, with no serious side effects observed after 3 to 24 months. Conclusions: WD can present as early as 2 years of age. Because biochemical tests may be less sensitive in very young children, diagnoses may require a combination of tests. If molecular tests are inconclusive, liver copper content should be measured.